2001
DOI: 10.1080/00036840010009883
|View full text |Cite
|
Sign up to set email alerts
|

The income effect and supplier induced demand. Evidence from primary physician services in Norway

Abstract: A much debated issue within the health economic literature is whether physicians can induce demand for their services. The relationship between physicians' ‘nonpractice income’ and supply of primary physician services in Norway is examined. It is argued that, if inducement exists, physicians with a low nonpractice income who work in municipalities where competition for patients is high, compensate for lack of patients by inducing demand. This model is adapted to the institutional setting of the Norwegian prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 26 publications
4
22
0
Order By: Relevance
“…Our results are also consistent with the findings from an earlier panel data study of primary physician services in Norway [21] The findings are also consistent with the results of other studies of primary physician 13 services in Norway in which cross-sectional data have been used [29][30][31][32]. A main finding in these studies is that increased competition (more physicians per capita) leads to lower physician income.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results are also consistent with the findings from an earlier panel data study of primary physician services in Norway [21] The findings are also consistent with the results of other studies of primary physician 13 services in Norway in which cross-sectional data have been used [29][30][31][32]. A main finding in these studies is that increased competition (more physicians per capita) leads to lower physician income.…”
Section: Discussionsupporting
confidence: 92%
“…They found that non-practice income had no effect on the number of treatment items per consultation. The results from the present study, which employs panel data rather than cross-sectional data, support the results from the study of Grytten et al [31].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The consumer price index is included for comparison. 9 We see that the basic consultation fee has not quite caught up with consumer prices, whereas the additional consultation fees, both for prolonged consultations and 7 Of course, if individuals move to another municipality they are also allowed to switch GP across municipalities. 8 The residual …ve percent of the GPs are basically publicly employed with regular salary contracts.…”
Section: Institutional Backgroundmentioning
confidence: 99%
“…However, later studies reveal more mixed …ndings. For example, a series of papers on Norwegian data (Grytten et al, 1995;2001;Carlsen et al, 2003Carlsen et al, , 2011 report little or no evidence of SID.…”
Section: Introductionmentioning
confidence: 99%